Pengaruh Pemadatan terhadap Sifat Fisis dan Mekanis Kayu Palapi - Hasan, Hajatni; Tatong, Burhan (Department of Civil Engineering, Diponegoro University, 2005)
The objective of this research is to study the effect of physical treatment, in this case is wood condensation to physical and mechanical properties of Palapi wood. In this research the wood condensation is compacted with heat treatment. Wood of Palapi accurate in form of board of tangensial of the size 2cm x 12cm x 36cm, compacted to radial direction. In this research the physical properties test is wood moisture content, wood density, and wood specific gravity. The mechanical test in this research is static elasticity strength of wood, firmness compressed parallelly of wood fibre and hardness of wood side. The properties test of physical and is mechanical were to Palapi wood plank without condensation and to palapi wood plank with condensation. The result of test indicate that wood of Palapi compacted have the nature of physical and better mechanical from which do not be compacted, that is moisture content rate downhill 58,85%, density and specific gravity wood mount 20,41%, wood elasticity modulus value mount 49,71%, modulus of rupture value mount 27,52%, assess firmness compressed parallelly of wood fibre mount 25,93%, assess hardness of side of tangensial mount 27,76%, assess hardness of side of radial mount 18,07%. This matter of indicate that with condensation hence quality of wood can mount goodness seen from strength and also its durability.Keywords: physical and mechanical of palapi woodPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3891[How to cite: Hasan, H. dan Tatong, B., 2005, Pengaruh Pemadatan terhadap Sifat Fisis dan Mekanis Kayu Palapi, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 1, pp. 1-15]